2018
DOI: 10.2174/1874350101811010184
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Tourism Behaviors: Enhancing the Influence of Tourists’ Perceptions on Local Thai Food and Culture

Abstract: Background: Tourist behavior plays a principle role in preserving the cultural heritage and supporting the economy of the local community. Local food is a significant factor for tourists and an important cultural aspect distinguishing one country from one another. To understand tourists' food decision making, this study investigates tourists’ perceptions of local food. Methods: A mixed-method methodology used a concur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
(74 reference statements)
1
4
0
Order By: Relevance
“…Meanwhile, GM is the most significant predictor of RI. This result is identical to that of Prapasawasdi et al (2018), where it was found that GM is the most crucial factor that influences tourists' behavioural intentions. In terms of contribution, the results offer insight into the behavioural intention of Malaysian Muslim tourists toward Japanese street food vendors.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
“…Meanwhile, GM is the most significant predictor of RI. This result is identical to that of Prapasawasdi et al (2018), where it was found that GM is the most crucial factor that influences tourists' behavioural intentions. In terms of contribution, the results offer insight into the behavioural intention of Malaysian Muslim tourists toward Japanese street food vendors.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
“…This presents a significant opportunity for Thailand's cultural tourism to contribute to the recovery of the country's tourism industry, strengthen its economy, and boost income in key tourist cities and neighboring regions once again. The studies on Thai cultural tourism are widely present such as Pookaiyaudom and Tan (2020), Prapasawasdi et al (2018), Kasemsarn and Nickpour (2017), Sukanthasirikul and Trongpanich (2016), but they tend to be central to cultural tourism activities from all parts of Thailand. Additionally, it is hardly seen in form of cultural shows, especially performed by LGBTQ+ performers.…”
Section: Discussionmentioning
confidence: 99%
“…Highlighting the interesting, distinctive, and beautiful aspects of Thai culture and incorporating them into communication through various means such as presentations and communication tools, personal media, architecture, homes, clothing, cuisine, lifestyle, traditions, and beliefs can contribute significantly to the development of tourism. By promoting these cultural aspects alongside contemporary tourism development, Thai culture becomes more recognized and contributes to both the economic and social wellbeing of the country (Richards 2020;Prapasawasdi et al 2018).…”
Section: Development Of Cultural Tourism In Thailandmentioning
confidence: 99%
See 1 more Smart Citation
“…Prapasawasdi et al ( 93 ) revealed that attitude, SN, perceived value, and expectation factors of Thai tourists had a positive effect on how they perceived local food information.…”
Section: Introductionmentioning
confidence: 99%